2022
DOI: 10.30574/wjbphs.2022.12.3.0234
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification, clinical assessment, characterization of SARS-CoV-2 RT-PCR results: Insights into twenty-one months of COVID-19 pandemic in a single center in Bangladesh

Abstract: Introduction: The pervasiveness of SARS-CoV-2 infection over millions of people renders a variety of symptoms among group of people and ages. This study aimed to appraise the clinical assessment, characterization, and comparative study on suspected SARS-CoV-2 infected patients and further illuminate its transmission dynamics. Methods: It includes all the suspected SARS-CoV-2 infected cases from July 2020 to March 2022 in this retrospective single center study. All the cases confirmed by the golden method of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…This complication was observed in both hospitalized and nonhospitalized patients, and in those admitted to in-patient wards and the ICU. Seven studies assessed the association between fatigue and COVID-19 severity [20,21] ; four found greater fatigue in severely ill individuals, and one study reported greater fatigue or physical decline with longer durations of hospital stay [22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
“…This complication was observed in both hospitalized and nonhospitalized patients, and in those admitted to in-patient wards and the ICU. Seven studies assessed the association between fatigue and COVID-19 severity [20,21] ; four found greater fatigue in severely ill individuals, and one study reported greater fatigue or physical decline with longer durations of hospital stay [22][23][24] .…”
Section: Discussionmentioning
confidence: 99%